Anormogomphus kiritshenkoi Bartenev, 1913 (Odonata: Gomphidae): a literature review of the variable spelling of the species epithet, choice of the correct spelling and notes on the type locality of the species - Schorr, Martin; Kosterin, Oleg E.; Borisov, Sergey N.; Marinov, Milen (Zootaxa, 2018)
The spelling of the specific name of an Anormogomphus species in its original description by Bartenev (1913) was variable, kiritshenkoi (5 times) vs kiritschenkoi (1 time). Bartenev himself did not mention this species in his further publications. Later authors proceeded to use different spelling versions of this name, including those not in the original paper. According to the International Code of Zoological Nomenclature (ICZN), the valid spelling should be chosen by the First Reviser. Acting as such, we choose as valid the name spelling Anormogomphus kiritshenkoi Bartenev, 1913, since it predominates in the original description, appears in the species subtitle, and is a proper transliteration from Cyrillic to Latin. It also corresponds to the spelling of his name used by A.N. Kiritshenko himself. Information of the type locality of the species is provided.